Periodic Solutions for Second-Order Ordinary Differential Equations with Linear Nonlinearity - Xiaohong Hu; Dabin Wang; Changyou Wang (Abstract and Applied Analysis)
By using minimax methods in critical point theory, we obtain the existence of periodic solutions for second-order ordinary differential equations with linear nonlinearity.